2009
DOI: 10.1007/s11547-008-0355-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of high-resolution ultrasonography without and with real-time spatial compound imaging in evaluating the injured posterior cruciate ligament: preliminary study

Abstract: HRUS is a reliable technique for studying the PCL and detecting PCL injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…It is widely used to diagnose ligament, tendon, and meniscus injuries and is a good modality for screening intra-articular lesions [ 12 , 14 , 15 ]. Some studies using ultrasonography have shown that the injured PCL is thicker than the contralateral non-injured PCL or the PCL of healthy people [ 16 , 17 ]. Wang et al recommended a thickness of ≥ 6.5 mm based on ultrasonography measurement as the diagnostic criteria for acute PCL injury (sensitivity 90.6%, specificity 86.7%) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used to diagnose ligament, tendon, and meniscus injuries and is a good modality for screening intra-articular lesions [ 12 , 14 , 15 ]. Some studies using ultrasonography have shown that the injured PCL is thicker than the contralateral non-injured PCL or the PCL of healthy people [ 16 , 17 ]. Wang et al recommended a thickness of ≥ 6.5 mm based on ultrasonography measurement as the diagnostic criteria for acute PCL injury (sensitivity 90.6%, specificity 86.7%) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Swelling (increased thickness) and softening (reduced pixel intensity) of injured PCLs were compatible with ligamentous injury pathological changes and were diagnostic of PCL injuries. Previous studies did not recommend a thickness cut‐off value for PCL injury, probably due to a limited case number [4, 12, 17, 22]. To the best of our knowledge, our study may represent the largest series of PCLs evaluated by US.…”
Section: Discussionmentioning
confidence: 90%
“…By contrast, ultrasonography (US) is a convenient, inexpensive, and non‐invasive modality for evaluating soft tissue injuries without radiation exposure. Several ultrasonographic studies found that injured PCLs were significantly thicker than contralateral uninjured PCLs and PCLs of healthy subjects [4, 12, 17, 22]. Cho et al recommended a PCL thickness >10 mm as a diagnostic criterion for an MRI‐confirmed acutely torn PCL [4].…”
Section: Introductionmentioning
confidence: 99%
“…In examining the characteristics of the studies collated in Table 1, we observed a diverse geographical representation across the included research, with authors from Taiwan, Korea, India, Italy, and Japan. The studies spanned over two decades, ranging from 1991 to 2017 [17][18][19][20][21][22][23]. The study by Wang CY et al conducted in Taiwan in 2009 was a retrospective cohort study and was appraised as having a fair study quality [17].…”
Section: Study Characteristicsmentioning
confidence: 99%